New methodical approach to the assessment of video record which is used when training of judoists - Konstantin Ananchenko; Alexander Khatsayuk (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to offer a new methodical approach for the assessment of video record which is used when training of judoists. Material & Methods: the assessment of video record, which is used in the course of training of judoists, was carried out in the research; the poll of 23 masters of sports of Ukraine and masters of sports of international class. Results: flexibility of a new methodical approach for the video record assessment is proved. Methodical approach assumes the use of unique mathematical apparatus - methods of pair comparisons and arrangement of priorities. It can be used for the assessment of video films for judoists of the various skill level, age, physical parameters for individual training of certain judoists at the correct selection of parameters of comparison. Conclusions: the use of the given methodical approach will promote the increase of efficiency of the competitive activity and coach's work, will allow judoists to reach high levels of individual skill.